Introducing artificial intelligence (AI)-based digital writing assistants for teachers in writing scientific articles - Samsul Khabib (Teaching English as a Foreign Language Journal, 2022)
Artificial intelligence (AI) technologies have played essential roles in the development of teachers. In recent years, AI-based digital writing assistants have received increasing attention among teachers. Thus, this study aims to know the use of AI-based digital writing assistants to help teachers write scientific articles. It used a sequential explanatory mixed methods study to gain the research data. Descriptive analysis was completed for the quantitative data, and thematic analysis was used for the qualitative data. The instrument used was surveys, consisting of pre and post-survey. Interestingly, the pre-survey found that teachers are not very familiar with digital writing assistants. Some of the participants had no prior knowledge of AI-assisted writing tools, while others only had limited experience. This means that more people need to be aware of the potential that AI offers in facilitating scientific writing. Furthermore, it is essential to teach teachers how to use this technology, as it can help them save time and effort while they write their articles. The post-survey conducted at the end of the project found that teachers found the process of writing a scientific article to be easier and more enjoyable with the help of AI. The results suggest that AI-based digital writing assistants may be able to provide an alternative method for teachers to compose their scientific articles. This tool could help to reduce errors and enable more efficient writing with greater accuracy. Additionally, the feedback suggests that AI-based tools could aid in improving students’ engagement and interest in writing.